Experimental semiotics : studies on the emergence and evolution of human communication - Galantucci, Bruno; Garrod, S. C. (Simon C.) (Benjamins current topics., 2012)
In the early twentieth century, Ferdinand de Saussure envisioned "a science which studies the role of signs as part of social life". About a century later, a science has emerged that is very much in the spirit of that envisioned by de Saussure. Researchers who are developing this science, which has been labeled Experimental Semiotics, conduct controlled studies in which human adults develop novel communication systems or impose novel structure on systems provided to them. This volume offers a primer to Experimental Semiotics and presents a set of studies conducted within this new discipline. T.